Jesus: God, the only God, or No God? A study of Jehovah’s Witnesses’ and Branhamism’s influence in Kolwezi, DRC - Mufika, Mathieu Bukasa (North-West University (South Africa) , Potchefstroom Campus, 2017)
This Christian apologetic thesis focuses on the question of the identity of Jesus. Is he God, the only God, or not God? The aim of the work is to bring back a Biblical understanding of basic Christian doctrines in Kolwezi and other places in the DRC and Africa in light of the influence of the teachings of the Jehovah’s Witnesses (JW) and Branhamites. The research starts with the history of Kolwezi, and this includes the people, culture, customs, behaviour and social life. Then it describes the introduction of Christianity in Kolwezi and follows its growth from colonial times until the independence of the DRC (1885-1960). The different periods of the country and city’s history, including the period of the Congo Free State (1885-1908); the Belgian Congo (1908-1960); the Democratic Republic of Congo (1960-1965); Congo-Zaire (1965-1997); and the Democratic Republic of the Congo (1997-2014), have all influenced the insight and understanding of Christianity and Christian doctrines. When the Christianity came to Kolwezi, it found the people involved in ancestors’ worship, practising magic powers in the indigenous communities. With this as background, the focus is on the religious life of the people in Kolwezi for the last fifty years. The research examines the influence of Arius by tracing the doctrines and the growth of the JW on the one hand. In 1985, this group had about 300 members, but today they are 37 times more (12 000 members). On the other hand, the research investigates the heresies of Sabellius (influential in the 2nd, 3rd, and 4th century) by tracing the beliefs of the Branhamites in and through the life and teachings of their prophet, William Marrion Branham. In Kolwezi, these two groups seized the opportunities provided by unstable situations such as the civil war (1960-65), tribal conflict (1961-63, 1992-93) and political crisis (1990-1991, 1998-2001, 2008-2012) to influence Christians in all walks of life with their end-time prophecies. The JW prophesied the end of the world several times (1914) and the Branhamites also (1977) prophesied the end time of the present world. While none of their prophecies have been fulfilled, their influence is spreading. This is in contradiction with the way Christians view the end time Christians believe according to Biblical prophecy that the second coming of Christ and the end of this era will be accomplished once and for all one day in the future. Not only their involvement in Kolwezi, but also the similarities between the JW and the Branhamites provide reasons to study them together. These similarities include this such as that both groups consider their founder to be a messenger of God; both see the organization as the only true church; both teach a Christology that differs radically from Christianity and the Bible; both deny the Trinity; both deny the bodily resurrection of Christ; both deny the personality of the Holy Spirit; both have wrongly prophesied the end time; both use manipulation techniques; and both deny the Apostles’ Creed. The thesis employs Christian apologetics to evaluate the two groups in an effort to understand what the task is and what method must be implemented so that the people of Kolwezi can be reintroduced to Jesus of the Bible.
free